Images of the Cooperativa Copacabana. An analysis of the shanty towns eradication and housing projects during the las military dictatorship through its photographs (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Between 1977 and 1979, the largest shanty town eradication plan in the history of the City of Buenos Aires was implemented. In this context, marked by violence and repression, new forms of organization emerged in the attempt to resist eviction policies. Among them, nine self-build housing cooperatives created in the same shanty towns that were being eradicated, whose purpose was the construction of neighborhoods in different suburban areas of Buenos Aires where they could relocate.This work focuses on the Cooperativa Copacabana of the Villa 31, which built La Asunción neighborhood in San Miguel, in the Province of Buenos Aires, and, specifically, on the analysis of its photographic archive. We focus on the different representations of the self-building of the neighborhood, the eradication of shanty towns, the members of the cooperative, their organization, the Catholic Faith, among other aspects.
Keywords: Eradication; Shanty town, Self-construction, Military dictatorship.